Within- and Between-Person Relationships Among Health, Awareness of Aging, and Control Beliefs: A Microlongitudinal Study. (24th October 2020) - Zhang, Shenghao; Neupert, Shevaun D
Abstract: Objective: Control beliefs are bidirectionally related to physical and cognitive health, and control beliefs are associated with awareness of aging (subjective age and awareness of age-related change [AARC]), but it is unclear how these processes unfold within persons over time. We examine these relationships from both between- and within-person perspectives. Methods: Older adults ( n = 116) ranging in age from 60 to 90 ( M = 64.71) completed a 9-day daily diary study online, resulting in 743 total days. Participants reported their sociodemographic characteristics on Day 1 and physical symptoms, memory failures, felt age, daily AARC gain and loss experiences, and control beliefs on Days 2–9. Results: Within-person deviations from one's typical awareness of aging (AARC losses, AARC gains, and subjective age) were associated with fluctuations in control beliefs. Multilevel mediation results showed that between-person AARC losses mediated the relationship between health (both physical symptoms and memory failures) and control beliefs, whereas both within- and between-person control beliefs mediated the relationship between physical health and AARC losses. Model fit comparisons showed that models with control beliefs mediating health and awareness of aging fit better than models with awareness of aging mediating health and control beliefs. Discussion: Our findings suggest that within-person physical and cognitive health indicators were associated with awareness of aging indirectly through control beliefs. Although between-person differences in AARC losses may link health and control beliefs, our results suggest that a more consistent pattern involves control beliefs linking health and awareness of aging.